Implementation of Online Marriage Management Information Systems in Improving Service Quality at the Office of Religious Affairs in Prambon District, Sidoarjo Regency - Yuliati, Andhini Rizki; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The aim of this research is to find out actually about the Implementation of the Online Marriage Management Information System in Improving the Quality of Service at the Prambon District Religious Affairs Office and the factors that become obstacles in implementing the Online Marriage Management Information System, namely the SIMKAH application. The method used in the research is qualitative research using a descriptive approach. The focus of the research is to emphasize the boundaries that will be studied, namely the implementation of a management information system in the religious affairs office using indicators of communication, resources, disposition and bureaucratic structure. The informant determination technique used was purposive sampling, consisting of the Head of KUA, staff and the bride and groom. Data collection techniques used by interviews, observation, and documentation. Data analysis techniques namely, data collection, data reduction, data presentation, and drawing conclusions. The research results show that the implementation of SIMKAH Online in improving services in the KUA Prambon District has been implemented as proven by the results of communication indicators, resource indicators, disposition indicators, and bureaucratic structure indicators, namely that they have been implemented. Thus it can be concluded that the implementation has been going well and effectively